Historical Consciousness and Its Importance in Instruction of Regional History - Krakora, Pavel; Kopecek, Pavel (Civilia, 2018)
This text deals with the basic concepts that are related to historical consciousness and regional history and also analyses their relationship. Moreover, it deals with the possibilities, challenges and opportunities that are offered by the regional history in relation to the educational process. In conclusion, some research projects focused on this theme are briefly presented.
Keywords: Regional History; Historical Consciousness; Teachers; Students; Schools; Field Didactics; Contemporary History